PENGUATAN ASPEK RELIGIUS MELALUI KEGIATAN BINA KARAKTER DI SMK NEGERI 8 SURAKARTA - Wahidatun Ni'mah Aprilia Sari; Achmad Muthali'in (Buletin Literasi Budaya Sekolah, 2023)
This study reviews the objectives of the character development activity concept and its application as a vehicle for improving student character in the school environment and the environment where they live. The subjects of this study were students, teachers and employees of SMK Negeri 8 Surakarta. The research data was taken from the results of observations, and interviews with several parties. The method in this study uses a qualitative description. This study describes the results that character building activities are carried out once a week on Tuesdays for 30 minutes, starting from 07.00-07.30 before the activity begins. Character building activities can also produce students to have noble character, be honest, moral, tolerant, care for others, work together, have faith, not only that, with character building activities once a week, it will provide anticorruption values since early to every student that is rife at this time. So that this activity is currently good and it is recommended for educations to continue to develop and carry out character building activities so that they become activities that have an impact on improving the quality of student learning and making students have good character.